2016
DOI: 10.1155/2016/8283257
|View full text |Cite
|
Sign up to set email alerts
|

Differential Characterization of Two Kinds of Stem Cells Isolated from Rabbit Nucleus Pulposus and Annulus Fibrosus

Abstract: Objective. Nucleus pulposus (NP) and annulus fibrosus (AF) are two main components of intervertebral disc (IVD). We aimed to figure out whether NP and AF also contain stem cells and whether these stem cells share common properties with chondrocytes and/or fibroblasts in their phenotypes or whether they are completely different types of cells with different characteristics. Design. The disk cells were isolated from AF and NP tissues of the same lumbar spine of the rabbits. The properties of these disk cells wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
0
14
1
Order By: Relevance
“…The low number of cells in the mature AF of advanced stages of senescence exclude them as a suitable cell source for the seeding of scaffolds. MSCs are a useful alternative cell type for annular repair and have been isolated from annular tissues of normal and degenerate IVDs . The cell clustering seen in the vicinity of annular defects is evidence of resident stem cell activity in these tissues .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The low number of cells in the mature AF of advanced stages of senescence exclude them as a suitable cell source for the seeding of scaffolds. MSCs are a useful alternative cell type for annular repair and have been isolated from annular tissues of normal and degenerate IVDs . The cell clustering seen in the vicinity of annular defects is evidence of resident stem cell activity in these tissues .…”
Section: Discussionmentioning
confidence: 99%
“…IVDs. [142][143][144][145] The cell clustering seen in the vicinity of annular defects is evidence of resident stem cell activity in these tissues. 146 The healing potential of the AF overall however is low with most of its intrinsic healing occurring at its outermost margins.…”
Section: The Ovine Large Lesion Model Of Disc Degeneration and Lbpmentioning
confidence: 99%
“…In 2009, Henriksson et al [ 22 ] applied the labeling technique in vivo and demonstrated the existence of slow-cycling cells and stem cell niche in the IVD region. After that, many groups isolated and identified MSCs from the nucleus pulposus, annulus fibrosus, and cartilage endplate [ 10 , 11 , 23 30 ]. In the present study, the cells isolated from NP had the following characteristics: (1) the cells presented with long spindle-shaped adherent growth and grew in a spiral formation; (2) the cells were positive for CD105, CD73, and CD90 and negative for CD34, CD14, CD19, and HLA-DR; and (3) the cells had the multilineage differentiation potential.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that stem cells play a key role in tissue regeneration and degeneration. Disc stem/progenitor cells have been isolated from human and animal spinal disc tissues [ 31 , 32 ]. AF stem/progenitor cells differ from AF fibroblasts in their ability to proliferate and self-renew, as well as in their multi-differentiation potential, which allows them to differentiate into various cell types such as adipocytes, chondrocytes and osteocytes, in addition to differentiating into AF fibroblasts.…”
Section: Discussionmentioning
confidence: 99%